2020
DOI: 10.1177/1557988320939731
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress is Associated with Reduced Sperm Motility in Normal Semen

Abstract: Infertility is among the most serious medical problems worldwide. Male factors contribute to 40%–50% of all infertility cases, and approximately 7% of men worldwide are affected by infertility. Spermatozoa are extremely vulnerable to oxidative insult. Oxidative stress results in axonemal damage and increased midpiece sperm morphological defects, which lead to reduced sperm motility. The aim of the study is to evaluate the association between sperm motility and the levels of selected antioxidants, cytokines, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 40 publications
5
69
0
3
Order By: Relevance
“…Negative correlation between the seminal plasma IL-17 level and sperm motility had been observed in our study, similar results had been reported by Qian et al [14] , it is thought that increased oxidative stress in seminal plasma induced by different cytokines could be the mechanism by which IL-17could impair sperm motility [15] . The significant increase in seminal plasma IL-17 level in patients with leukocytospermia observed in our study may shed light on the role of IL-17 in the pathogenesis of infertility induced by urogenital infection.…”
Section: Discussionsupporting
confidence: 92%
“…Negative correlation between the seminal plasma IL-17 level and sperm motility had been observed in our study, similar results had been reported by Qian et al [14] , it is thought that increased oxidative stress in seminal plasma induced by different cytokines could be the mechanism by which IL-17could impair sperm motility [15] . The significant increase in seminal plasma IL-17 level in patients with leukocytospermia observed in our study may shed light on the role of IL-17 in the pathogenesis of infertility induced by urogenital infection.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the interleukin 10 pathway was up-regulated in samples obtained after COVID-19 infection. Kurkowska et al (36) showed that elevated interleukin 10 was associated with reduced sperm motility in normal semen, which is in agreement with previous findings.…”
Section: Discussionsupporting
confidence: 89%
“…Even though infertile men present lower seminal plasma antioxidant capacity [ 79 , 227 ], oxidative damage in spermatozoa is mostly associated with exacerbated levels of ROS as opposed to impaired superoxide scavenging activity [ 211 ]. Loss of motility is one of the major consequences of oxidative stress in spermatozoa [ 228 ], arising from a combination of reduced membrane fluidity, due to dysregulated lipid peroxidation [ 229 ], and defective axonemal phosphorylation [ 230 , 231 , 232 ]. Furthermore, oxidative stress has been associated with spermatozoa DNA damage.…”
Section: The Potential Role Of Ucps On Diabesity-induced Male Infertilitymentioning
confidence: 99%